Ecotoxicological tests of diesel contaminated soil subjected to degradation by Eisenia fétida (Research, Society and Development, 2020)
Problems related to contaminated areas are growing increasingly, such as inadequate disposal of oil residues and leakage of fuel storage tanks, and often these areas are close to ecosystems, causing negative impacts on the environment. The objective of this work was to carry out preliminary tests according to the ISO draft, which is based on the behavioral test to test the soil quality and toxicity of Aromatic Polycyclic Hydrocarbons (APHs) with the species Eisenia fétida. These assays are used to evaluate the efficiency of a bioremediation process and / or to assess contamination of areas. The efficiency of a bioremediation process and / or the assessment of contamination of areas has been performed only with the aid of chemical parameters, without the insertion of ecotoxicological evaluation. Thus the ecotoxicological test can be applied as a rapid method to determine the bioavailability of soil contaminants for Eisenia fétida, where leakage behavior is used as an indicator. Soil samples doped with different concentrations of diesel oil were analyzed by the behavior test. The toxicity of diesel by the species was later confirmed by the lethality tests. The results showed that contents higher than 0.01% are lethal for Eisenia fétida earthworm. For contents higher than 0.05%, the species escaped from the section containing the contaminated soil to the control soil, indicating that the soil may be considered toxic above this value. It is also noted that the addition of organic matter increased the resistance of the earthworm to the amount of diesel.